Design and Implementation of an Automatic Gate for Cars at Railway Crossings - Damilare L. ADEKEYE; Isiyaku SALEH; Yemisi E. AKINSELI (FUDMA Journal of Engineering and Technology, 2025)
The growing volume of vehicular traffic at railway crossings has heightened the demand for advanced safety measures to prevent accidents and collisions between trains and vehicles. This project presents the design and implementation of an automated railway crossing gate system, developed to enhance safety and minimize human intervention. The proposed system utilizes infrared (IR) proximity sensors to detect the presence and movement of trains, enabling the timely closure and reopening of crossing gates. When a train approaches, the entrance IR sensor detects its presence and triggers the immediate closure of both gates, preventing vehicles and pedestrians from entering the crossing. Once the train has fully passed, the exit IR sensor detects its absence and signals the gates to reopen promptly, thus minimizing unnecessary traffic delays while ensuring maximum safety. The system’s performance was evaluated using response time metrics, which measure the interval between train detection and actuator activation (buzzer, LEDs, and gate mechanism). The prototype achieved an overall response time of 4.6 seconds, with delay times ranging between 0.5 and 2.1 seconds, demonstrating high sensitivity and operational efficiency. These findings confirm the system's capability to respond swiftly and accurately under real-world conditions. This work presents a cost-effective, responsive, and reliable solution for railway safety infrastructure, offering significant potential to reduce accidents and enhance safety at level crossings through the use of automated train detection and gate control.
Keywords: Railway crossings, accident, IR sensor, automatic gate, Atmega328P.